Генетическая дифференциация болотных и суходольных популяций Pinus sibirica по данным SSR-маркеров - Орешкова, Н.В.; Сидельникова, Т.С.; Пименова, А.В.; Ефремов, С.П. (Фактори експериментальної еволюції організмів, 2014)
Aims. The evaluation of population structure of bog and dry land populations of Siberian pine (P. sibirica) in Western Siberia was studied by markers of a nuclear genome. Methods. Six pairs of nuclear microsatellite loci were used for this analysis. 30 allelic variants were detected in 120 individuals of four populations of P. sibirica. Results. The most essential genetic distinctions were observed between of P. sibirica population from oligotrophic bog and the group of populations from a dry land, eutrophic bog and near settlement P. sibirica forest (Fst = 0.019; Dn = 0.053). The differentiation of West Siberian populations of P. sibirica on SSR markers exceeded 2.4% (Fst = 0.024). Conclusions. The studied populations differ on the genetic structure due to various environmental conditions of ecotopes.

Key words: populations of Pinus sibirica, microsatellite loci, genetic differentiation.